Towards a progressive agenda for the EU - (:unkn) unknown (My University, 2020)
The European Union is facing serious challenges that test its solidarity and unity in the age of insecurity and anxiety. The Eurozone debt crisis, the socalled “migration crisis” and recently the health crisis and economic downturn instigated by COVID-19 have posed the most formidable challenges to the European project and the EU member states. Given a series of crises and challenging questions facing the EU in less than a decade, it seems timely to discuss and evaluate a progressive vision for the future of the EU. This paper argues that the pandemic has shown the importance and urgency of the core progressive objectives and opened a window of opportunity for progressive politics to advance a new agenda for the EU based on social justice, inclusiveness, equality, and pluralism. This new agenda has the potential to rejuvenate European integration while also allowing the progressives to confront the rise of the radical right in Europe. The paper particularly seeks to address to what extent progressive politics could shift the political agenda away from migration and security issues, create a new movement based on new thinking and a narrative in the face of COVID-19 and take an active part in the transformation of European politics and the EU.

Avrupa Birliği, güvensizlik ve endişe çağında dayanışmasını ve birliğini sınayan ciddi zorluklarla karşı karşıyadır. Euro bölgesi borç krizi, sözde "göç krizi" ve son zamanlarda COVID-19'un neden olduğu sağlık krizi ve ekonomik sorunlar, Avrupa projesi ve AB üye ülkeleri için önemli zorluklar oluşturmaktadır. AB'nin on yıldan kısa bir süre içinde karşı karşıya kaldığı bir dizi kriz ve zorlu sorular göz önüne alındığında, AB'nin geleceği için ilerici bir vizyonu tartışmak ve değerlendirmek için en doğru zamanda bulunmaktayız. Bu makale, pandeminin ilerici siyasetin temel hedeflerinin önem ve aciliyetini gösterdiğini ve ilerici siyasetin AB için sosyal adalet, kapsayıcılık, eşitlik ve çoğulculuğa dayanan yeni bir gündem geliştirmesi için bir fırsat penceresi açtığını ileri sürmektedir. Yeni ilerici gündem, Avrupa entegrasyonunu yeniden canlandırma potansiyelini taşırken, aynı zamanda ilerici siyasetin Avrupa'da radikal sağın yükselişiyle yüzleşmesine olanak tanıyacaktır. Makale ilerici siyasetin siyasi gündemi göç ve güvenlik sorunlarından uzaklaştırabilmesinin, COVID-19 karşısında yeni düşünceye dayalı yeni bir hareket ve bir anlatı yaratabilmesinin ve Avrupa siyaseti ve AB’nin dönüşümünde etkin rol alabilmesinin imkanlarını ele almaktadır.
AB için ilerlemeci bir ajandaya doğru mu
Keywords: AB; ilerlemeci siyaset; sosyal Avrupa; uluslararası göç; neoliberal küreselleşme; COVID-19; EU; progressive politics; social Europe; international migration; neoliberal globalization